AGAINTS CRISIS MELALUI ENTREPRENEURSHIP - Hesti Respatiningsih (FE Program Studi Manajemen, 2006)
One of the effort which is done by our nation to against the crisis is entrepreneurship. It will take a role in creating the entrepreneur who has a competence to assist himself/herself to overcome his/her life in any conditions and afford to help the other person or society by giving employments, educating the social to be more innovative and creative in order to get product/service which is necessary for the society, and creating the social capital which are understanding each other, trusty and raising of cooperative attitude. Keywords: againts crisis, entrepreneurship, entrepreneur